Vrednost znanja jezika v gospodarstvu - Novak-Lukanovič, Sonja (Teorija in praksa, 2020)
Based on selected results of empirical research, the paper aims to highlight the importance of the Slovenian language and the role of foreign languages in relation to economic variables. The research results confirm that the economy influences both the choice and use of language in specific, economic-category-related situations, meaning that economic variables also affect the status of the Slovenian language in companies established in Slovenia. Various theoretical concepts linking language and the economy are presented, with a stress on Slovenian authors who wrote about and pointed to the connection between language and economy in the past. The central part of the paper presents the results of the empirical phase of the research project, which included interviews with executives in various companies in Slovenia and neighbouring countries - Italy, Austria and Hungary. The main research topics include the value of proficiency and use of language (Slovenian, minority language, foreign language). The results reveal that the value of language proficiency is closely connected to its economic effects for the particular company
Keywords: business; economy; empirical research; empirična raziskava; gospodarstvo; jezikovne prakse; podjetja; poslovni jezik; Slovenian; Slovenian in public; slovenščina v gospodarstvu; value of language proficiency; vrednost jezika; znanje jezika